The role of family physicians in emergency and essential surgical care in the district health system in South Africa - Kathryn Chu; Priyanka Naidu; Steve Reid; Hans Hendriks; Jenny Nash; Vanessa Lomas; Francois Coetzee; Robert Mash (South African Family Practice)
No abstract available.